1997
DOI: 10.1001/archsurg.1997.01430260064014
|View full text |Cite
|
Sign up to set email alerts
|

Gasless Laparoscopy May Reduce the Risk of Port-Site Metastases Following Laparascopic Tumor Surgery

Abstract: The use of laparoscopy without gas insufflation may reduce the risk of wound metastasis following laparoscopic surgery for cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(93 citation statements)
references
References 13 publications
0
89
0
4
Order By: Relevance
“…Similar results were achieved by the same authors with a cell suspension of CC531. 34 These results are supported by Watson et al, 37 who demonstrated that the incidence of port-site metastases in a rat model was reduced after gasless laparoscopy compared with insufflation with CO 2 .…”
Section: Discussionmentioning
confidence: 57%
“…Similar results were achieved by the same authors with a cell suspension of CC531. 34 These results are supported by Watson et al, 37 who demonstrated that the incidence of port-site metastases in a rat model was reduced after gasless laparoscopy compared with insufflation with CO 2 .…”
Section: Discussionmentioning
confidence: 57%
“…A cytology sampling was obtained, which did not influence therapeutic decisions. Mean exploration time was 22 minutes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). If the tumor was considered curable, the trocars were withdrawn and a laparotomy and radical gastrectomy were performed.…”
Section: Methodsmentioning
confidence: 99%
“…As a result, studies have been addressed concerning the influence of laparoscopy on tumor spreading and patient survival. They suggest a role for CO 2 diffusion (16)(17)(18)(19)(20)(21)(22), limited surgeon experience and consequent tumor handling (21,23), direct cell adhesion to ports (24), trocar material composition (25), and hematogenous spread (26,27). At present controversy persists.…”
Section: Introductionmentioning
confidence: 99%
“…ст., использовании специальных герметичных троакаров, извлечении препарата в контейнере и ушивании по-слеоперационных ран [12][13][14]. Подобная техника применяется в онкологических клиниках, но и она не позволила избежать возникновения рецидивов.…”
Section: опухоли женской репродуктивной системы Tumors Of Female Reprunclassified